Factors Differentiating Poles’ Attitudes Towards Social Relations – a Spatial Approach - Szubert, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The research focuses on Poles’ attitudes towards selected aspects associated with social relations. Responses to the following 6 statements were examined: 1 – People try to help others above all, 2 – Homosexuals should be allowed to live according to their beliefs, 3 – Foreigners have too much to say in our country, 4 – Some people are worth more than others, 5 – Some groups of persons are not worthy of respect, 6 – We should seek to make the income of all persons more or less equal. The first aim of the study was to check how the level of agreement with those statements was distributed spatially in terms of districts. Then it was checked whether those attitudes were differentiated by 8 characteristics describing Poles: sex, marital status, education level, health status, participation in church services, age and income level, also taking into account the spatial aspect. Finally, regression models (classical and spatial) were constructed to check whether several features describing districts (rather than individual respondents) could help to build a model explaining why in some regions the population agreed with the statements more and in other areas less. The data needed for the analysis were taken from the nationwide study entitled “Social Diagnosis” and all calculations were carried out in the PQStat and Geoda programmes.